Du dandisme au nazisme: intersezioni e coincidenze - Canzaniello, Emanuele (Status Quaestionis, 2013)
This article aims to investigate the relationships between the apparently irreducible categories of dandyism and Nazism, associated since Dominique Desanti’s brilliant formulation: “du dandisme au nazisme”. Therefore, the discussion will be about the symmetric interaction of these two concepts and their cultural forerunners; the essay will focus on the opposition between Revolution and Conservatism, from a logical and semantic point of view, as conveyed by the historical and philosophical category of Conservative Revolution. My argument is sustained by the well known study by Jean Pierre Faye, Théorie du récit. Introduction aux “langages totalitaires”, an attempt to supply some essential genealogies in the reconstruction of totalitarian aesthetics.